Odpowiedź :
Odpowiedź:
a)2x+9=15
2x = 15-9
2x= 6/÷2
x= 3
b)4x-7=x+5
4x-x= 5+7
3x= 12/÷3
x=4
c)2(x+2)=x-6
2x+4= x-6
2x-x= -6-4
x= -10
d)3x-4=8
3x = 8+4
3x= 12/÷3
x= 4
e)5x-6=x+8
5x-x=8+6
4x = 14/÷4
x= 3 1/2
Odpowiedź:
a) 2x+9= 15
2x= 15-9
2x=6 /:2
x=3
spr... 2*3 +9= 15
6+9= 15
15=15
L=P
b) 4x-7 = x+5
4x-x= 5+7
3x=12 /:3
x=4
spr.. 4*4 -7= 4+5
16-7= 9
9=9
L=P
c) 2 ( x+2) = x-6
2x+4= x-6
2x-x= -6 -4
x= - 10
spr... 2*(-10) +4= -10-6
-20+4= -16
-16= - 16
L=P
d) 3x-4= 8
3x= 8 +4
3x=12 /:3
x=4
spr... 3*4- 4=8
12-4=8
8=8
L=P
e) 5x-6 = x+8
5x-x= 8+6
4x = 14 /:4
x= 14/4= 3 i 2/4= 3 i 1/2
spr... 5*14/4 -6= 3 i 1/2 +8
70/4-6= 11 i 1/2
17 i 1/2- 6= 11 i 1/2
11 i 1/2= 11 i 1/2
L=P
Szczegółowe wyjaśnienie: